Efektivitas Perubahan Target Pencapaian Pajak Kendaraan Di Badan Pendapatan Daerah Provinsi Sumatera Selatan - Nasrudin, Ahmad; Lisdiana, Lisdiana; Asteriniah, Femi (@-Publik: Jurnal Administrasi Publik, 2025)
The South Sumatra Provincial Revenue Agency is a local agency specifically tasked with managing local revenue sources in the government's efforts to collect funds for regional development tasks. One of the taxes with suboptimal revenue collection is the Motor Vehicle Tax, as many taxpayers are not aware of their obligations, resulting in the Motor Vehicle Tax collection not meeting the established target. The problem with motor vehicle tax collection is the frequent miscalculations made by taxpayers when purchasing vehicles. Taxpayers are also unaware of the rules concerning regular payments of the Motor Vehicle Tax when they sell motor vehicles. Consequently, when it comes to tax payments, taxpayers are more inclined to wait for the tax exemption process, hoping to avoid fines for late payment of their vehicle taxes. The purpose of this research is to evaluate changes in the Vehicle Tax collection target at the South Sumatra Provincial Revenue Agency. Based on the research results, the evaluation of the implementation of the Regional Revenue and Expenditure Budget (RKA SKPD) documents in the Musi Banyuasin Regency, considering the contextual aspect, is considered to be good as it meets the intended goals and has clear implementation objectives. However, in terms of input, it is known that there are limitations due to the lack of supporting infrastructure for the preparation and implementation of RKA documents. In terms of the process, there are challenges, including frequent network issues in inputting RKA into the budget application, and discrepancies in the schedule of public deliberations (musrenbang), which often lead to delays in preparing budget documents. As for the product aspect, it is known that the Work Plan documents at the Musi Banyuasin Regency Planning and Development Agency are available as a reference and guide for development implementation.